Fire from heaven - Renault, Mary. (New York : Vintage Books, 1977)
A narrative of the life of Alexander the Great from his childhood to the age of twenty when he succeeded his murdered father, King Philip of Macedon.
Wilson's Fiction.
Young Adult
Keywords: Alexander, -- the Great, -- 356-323 B.C. -- Fiction; Philip -- II, -- King of Macedonia, -- 382-336 B.C. -- Fiction; Alexander, -- the Great, -- 356-323 B.C. -- Fiction; Philip -- II, -- King of Macedonia, -- 382-336 B.C. -- Fiction; Generals -- Greece -- Fiction; Generals -- Fiction; Historical fiction; Greece -- Kings and rulers -- Fiction; Macedonia -- Kings and rulers -- Fiction; Greece -- Kings and rulers -- Fiction; Macedonia -- Kings and rulers -- Fiction; Biographical fiction